Unified Active and Reactive Power Coordinated Optimization for Unbalanced Distribution Networks in Radial and Looped Topology - Zeng, Yuanjing; Wang, Yang; Li, Peishuai (Frontiers in Energy Research, 2022)
Facing the high proportion of distributed generations incorporating in single phase, the active distribution network has become more unbalanced with flexible topology. In this paper, a unified active and reactive power coordinated optimization (ARPCO) method which is applicable in both radial and looped unbalanced distribution network is proposed. Aiming to reduce power losses and restrain undervoltage and overvoltage problem, the ARPCO model which regulates the active and reactive power output of distributed generations coordinately and optimally is constructed. A novel trust region sequential linear programming (SLP) method which is effective in nonlinear and nonconvex model solving is developed and employed in APRCO model solution. Multi-scenarios case study based on modified IEEE 123 node distribution system shows that the proposed method is able to reduce the system active power loss and solve under-voltage and over-voltage problem efficiently, at the same time maximizing the utilization of distributed generations.